Differential response of three large mammal species to human recreation in the Rocky Mountains of Colorado, USA - Uetrecht, Madison R.; Bermudez, April; Novoa, Daniel; Reithel, Jennifer; Rodriguez, Vaneza; Smith, Rosemary; Sprott, Shannon; Tingley, Morgan W.; Blumstein, Daniel T. (Frontiers in Conservation Science, 2023)
Outdoor recreation benefits local economies, environmental education, and public health and wellbeing, but it can also adversely affect local ecosystems. Human presence in natural areas alters feeding and reproductive behaviors, physiology, and population structure in many wildlife species, often resulting in cascading effects through entire ecological communities. As outdoor recreation gains popularity, existing trails are becoming overcrowded and new trails are being built to accommodate increasing use. Many recreation impact studies have investigated effects of the presence or absence of humans while few have investigated recreation effects on wildlife using a gradient of disturbance intensity. We used camera traps to quantify trail use by humans and mid-to large-sized mammals in an area of intense outdoor recreation--the Upper East River Valley, Colorado, USA. We selected five trails with different types and intensities of human use and deployed six cameras on each trail for five weeks during a COVID-enhanced 2020 summer tourism season. We used occupancy models to estimate detectability and habitat use of the three most common mammal species in the study area and determined which human activities affect the habitat use patterns of each species. Human activities affected each species differently. Mule deer (Odocoileus hemionus) tended to use areas with more vehicles, more predators, and greater